PRIMARY RESPONSIBILITIES OF THE UN SECURITY COUNCIL UNDER ARTICLES 24-25 OF THE CHARTER: A COMPREHENSIVE LITERATURE REVIEW ON THE LEGAL FORCE OF BINDING DECISIONS, MEMBER STATES' OBLIGATIONS TO COMPLY, AND THE STRATEGIC ROLE IN CONFLICT PREVENTION AND CONTEMPORARY INTERNATIONAL DISPUTE RESOLUTION - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2026)
This study analyses the primary responsibilities of the UN Security Council under Articles 24-25 of the UN Charter through a literature review examining the legal force of binding decisions under Article 25, which explicitly requires member states to accept and implement Chapter VII resolutions such as Resolution 1373 (anti-terrorism) and 1718 (North Korea). compliance obligations that include national legal adjustments and sanctions committee reporting, as well as a strategic role in conflict prevention through Article 34 investigations and Chapter VI peace recommendations, along with contemporary dispute resolution via peacekeeping and Article 41 sanctions amid the challenges of the P5 veto and representation disparities. with key findings affirming the superiority of binding norms despite limited effectiveness due to geopolitical politicisation requiring structural reform for relevance in the multipolar era